Scanning ion conductance microscopy: a nanotechnology for biological studies in live cells - Liu, Bing-Chen; Lu, Xiao-Yu; Song, Xiang; Lei, Ke-Yu; Alli, Abdel A.; Bao, Hui-Fang; Eaton, Douglas C.; Ma, He-Ping (Frontiers in Physiology, 2013)
Scanning ion conductance microscope (SICM), which enables high-resolution imaging of cell surface topography, has been developed for over two decades. However, only recently, a unique scanning mode is increasingly used in biological studies to allow SICM to detect the surface of live cells. More recently, in combination with confocal microscopy and patch-clamp electrophysiological techniques, SICM allows investigators to localize proteins or ion channels in a specific nanostructure at the cell surface. This article will briefly review SICM nanotechnique and summarize the role of SICM in biological studies.